Pengaruh Lingkungan Keluarga Dan Proses Pembelajaran Di Perguruan Tinggi Terhadap Literasi Keuangan (Studi Kasus Pada Mahasiswa Sekolah Tinggi Manajemen Labora) - Dewi Kartikaningsih; Syamsu Yusuf (Jurnal Co Management, 2020)
This study aimed to analyze the influence of family environment and learning in college education toward financial literacy of Labora School of Manajemen students in Jakarta. This study uses a quantitative approach to comparative causal type. Based on the calculation of sampling using a purposive sampling method with Slovin formula obtained a minimum of 62 respondents so that the respondents get the final data. The method used is a survey method using a questionnaire given to students and answered by students and processed with a Likert scale. Data analysis techniques used are multiple linear regression. Based on the results of the analysis that has been done, the results show that the family environment, college learning has a positive and significant effect on financial literacy with a linear regression equation in this study formulated with Y = 2.054 + 0.419 X1 + 0.470 X2. The results of the study are partially family environment and learning in college education influence financial literacy and simultaneously family environment and learning in college education influence financial literacy.